Immunological Hallmarks of Inflammatory Status in Vaso-Occlusive Crisis of Sickle Cell Anemia Patients - Silva-Junior, Alexander Leonardo; Garcia, Nadja Pinto; Cardoso, Evilázio Cunha; Dias, Stephanny; Tarragô, Andrea Monteiro; Fraiji, Nelson Abrahim; Gomes, Matheus Souza; Amaral, Laurence Rodrigues; Teixeira-Carvalho, Andréa; Martins-Filho, Olindo Assis; De Paula, Erich Vinicius; Costa, Allyson Guimarães; et al. (Frontiers in Immunology, 2021)
Sickle Cell Anemia (SCA) is the most common genetic disorder around the world. The mutation on β-globin gene is responsible for higher hemolysis rate, with further involvement of immunological molecules, especially cytokines, chemokines, growth factors and anaphylatoxins. These molecules are responsible to induce and attract immune cells to the circulation thus contributing to increases in leukocytes and other pro-inflammatory mediators, which can culminate in a vaso-occlusive crisis (VOC). This study aimed to characterize the levels of these molecules in SCA patients in different clinical conditions so as to identify potential hallmarks of inflammation in these patients. An analytical prospective study was conducted, using serum of SCA patients in steady-state (StSt; n=27) and VOC (n=22) along with 53 healthy donors (HD). Samples from the VOC group were obtained at admission and at discharge, in the convalescent phase (CV). Levels of chemokines (CXCL8, CXCL10, CL2, CLL3, CCL4, CL5 and CCL11), cytokines (IL-1β, IL-1ra, IL-2, IL-4, IL-5, IL-6, IL-7, IL-10, IL-12p70, IL-13, IL-17A, TNF-α, and IFN-γ) and growth factors (VEGF, FGFb, PDGF-BB, GM-CSF and G-CSF) were measured by Luminex assay, while anaphylatoxins (C3a, C4a and C5a) were measured by Cytometric Bead Array. SCA patients in StSt condition showed a pro-inflammatory profile, marked as higher producers of CCL2, IL-1β, IL-12p70, IFN-γ, IL-17A and GM-CSF, while VOC is highlighted by molecules IL-4 and IL-5, but also IL-2, IL-7, PDGF-BB and G-CSF. PDGF-BB and IL-1ra seemed two important hallmarks for acute-to-chronic stage, due to its significant decrease after crisis inflammation and statistical difference under VOC and CV groups. These molecules show higher levels and a strong correlation with other molecules in VOC condition. Besides they remain increased even after crisis recovery, which suggest their importance on inflammation role in crisis and participation on immune cells adhesion and activation. These results support a relevant role of cytokines, neutrophil and monocytes, which may act as markers of VOC inflammation in SCA patients.